The effects of relaxation exercises on EMG index of national judo athletes - Khorand, M.; Ashayeri, H.; Bagherzadeh, F. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Success in sport requires both physical and psychological skills and stress management and the athletes` ability to cope with mental stress using various psychological tools or mental skills is critical to their performance. To test the efficacy of relaxation exercises as a tool in alleviating mental stress a study was conducted involving 20 national level judo athletes. The results were evaluated using the EMG index and a questionnaire following an 8-week intervention which incorporated relaxation exercises into the training program. The results of the survey indicated that the relaxation exercise intervention was successful in lowering mental stress and had a significant effect on the EMG index.